Systematic identification of needlefish (Belonidae) species using molecular genetic and morphological markers in the Mediterranean and Black Seas - Cemal Turan; Petya Pavlova Ivanova; Servet Ahmet Doğdu; Deniz Ergüden; Violin Stoyanov Raykov; Maria Yankova; Deniz Yağlioğlu; Ayşegül Ergenler (PLoS ONE, 2025)
In this study, we aimed to clarify the taxonomic status of Belonidae species distributed in the Mediterranean Sea and the Black Sea by conducting detailed genetic and morphological markers. A total of 550 needlefish samples were caught between January 2022 and January 2024. The data set used in the study contains a total of 171 sequences for the COI gene and 120 sequences for the 12s rRNA gene from different Belonidae species, including data from GenBank. Systematic analysis of needlefish species was investigated by using sequencing of mtDNA COI and 12s rRNA gene regions and morphological characters in the Turkish Marine Waters. A separate analysis of the two mitochondrial genes supported by morphological characters revealed that each species is grouped within itself. The genetic and morphological analyses showed that Belone belone acus and Belone belone euxini which are considered as the subspecies of Belone belone are not subspecies of the genus Belone and should be considered at the species level, Belone belone. Belone svetovidovi is also considerably different from Belone belone and should be considered as a different species. T. acus imperialis, which is thought to be distributed in the Mediterranean Sea, is not a subspecies of Tylosorus acus and should be revised as Tylosorus imperialis which genetically differs from Tylosorus acus and also other Tylosorus species at the species level.